Oral and dental management in children with tetralogy of fallot - Arlette Suzy Puspa Pertiwi; Inne Suherna Sasmita; Yetty Herdiati Nonong (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Tetralogy of fallot is one of the congenital cyanotic heart disease that is often found in children. The disorder has four features, a ventricular septal defect, aortic overriding, infundibulary stenotic, and hypertrophy right ventricular. Like other congenital heart disease, tetralogy of fallot sometimes related to fatal complications, such as bacterial endocarditis which was related to dental infections. The correct management of oral and dental conditions is important to prevent bacterial endocarditis. This paper discussed the oral and dental conditions and its management in two cases of tetralogy of fallot children.